Integrated Approach For Production Planning And Sequencing Decisions In A Single Machine Batch Process - Suppiah, Yasothei (2005)
This thesis is motivated by a planning and scheduling decision problem encountered in a multi-product batch operations of a chemical firm in Malaysia. Batch processing means the processing of an integrated, non-divisible unit product such as volume of resin, polymer, or specialty chemical products. The objective of this research is to develop a practical solution approach for an industrial size problem that integrates production planning and sequencing decisions that involves multiple products, single machine in a multipurpose batch chemical manufacturing environment. Hence, a hierarchical framework which consists of three levels is developed which integrates the production planning and sequencing decisions which can answer to the management questions: "which product to make in which periodsand the exact production sequence that meet customer's due date?"